From Corporatism to Public Utilities: Workplace Pensions in the 21st Century. - Clark, G (Blackwell Publishing, 2012)
For many Organisation for Economic Cooperation and Development countries, workplace pensions have been an important mechanism for supplementing state-sponsored social security. Notwithstanding significant differences between developed economies in the significance attached to workplace pensions, provision has been typically encouraged through preferential tax policies on benefits and compensation packages. If relevant for the baby-boom generation, it is doubtful that these arrangements will be as important for future generations. As state-sponsored social security has been discounted in terms of promised value and entitlement, traditional workplace pensions have been closing and replaced by retirement saving instruments that are neither as lucrative nor as dependable. Retrenchment in workplace pensions has prompted governments to consider and, in some cases, develop different types of retirement savings institutions. This paper charts the decline of traditional workplace pensions, the apparent inadequacy of alternatives such as money-purchase (defined contribution) schemes, and the rise of what are referred to as ‘public utilities’: government sponsored savings institutions designed to compensate for the decline (in coverage and promised value) of workplace pensions albeit at a more modest level than that associated with traditional defined benefit schemes. Reference is made to the experience of the USA, the UK, and Australia with passing comments of related developments in Germany and continental Europe. It is argued that the rise of public utilities in this domain is indicative of the transformation of corporate capitalism over the past 25 years and the realisation that the costs of neoliberalism may be so significant that governments have to take responsibility, once again, for underwriting retirement welfare.